Lessons from the Tequila Crisis - Mishkin, Frederic S. (Journal of Banking & Finance, 1999)
This paper draws several important lessons from the Tequila Crisis of 1994 and 1995. The overriding lesson is that the dynamics of financial crises in emerging market countries differ from those in industrialized countries because institutional features of their debt markets differ. Several policy lessons for emerging market countries also emerge from the analysis: (1) pegged exchange-rate regimes are extremely dangerous, (2) strong prudential supervision of the banking system is critical for prevention of financial crises, (3) financial liberalization must be managed extremely carefully and (4) different policies are needed to promote recovery in emerging market countries than those that are applicable to industrialized countries.